Synergistic combination of duloxetine hydrochloride and fluconazole reduces the cell growth and capsule size of Cryptococcus neoformans - Menezes, Raquel T. [UNESP]; Pereira, Thaís C. [UNESP]; Junqueira, Juliana C. [UNESP]; Oliveira, Luciane D. [UNESP]; Scorzoni, Liliawna [UNESP] (FapUNIFESP (SciELO), 2022)
This study aimed to evaluate the effect of duloxetine hydrochloride (DH) on Cryptococcus neoformans. DH minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) were 18.5 µg/mL, and the combination with fluconazole (FLZ) reduced the MIC value by 16-and 4-fold for DH and FLZ, respectively. The capsule size decreased by 67% and 16% when treated with DH and DH with FLZ, respectively. Therefore, this study showed that DH is active against C. neoformans alone and in combination with FLZ, leading to the reduction of the capsule size of this yeast.
Keywords: Capsule; Cryptococcus neoformans; Duloxetine hydrochloride; Fluconazole; Synergistic combination